Parameter extraction of PV modules using particle swarm optimization / Maruwan Mohammed Khalleeffah Alqishat. - Alqishat, Maruwan Mohammed Khalleeffah (School of Electrical System Engineering, Universiti Malaysia Perlis, 2017)
The research objectives stated as follow ; to develop an efficient optimization-based strategy for constructing a model for PV module ; to develop model validation tools to help assess the validity and preciseness of the obtained model given the experimental data ; to assess the capabilities and limitations of single diode model in providing an exact model of PV module.